Allergic Rhinitis: A Clinical and Pathophysiological Overview - Nur Husna, Siti Muhamad; Tan, Hern-Tze Tina; Md Shukri, Norasnieda; Mohd Ashari, Noor Suryani; Wong, Kah Keng (Frontiers in Medicine, 2022)
Allergic rhinitis (AR) represents a global health concern where it affects approximately 400 million people worldwide. The prevalence of AR has increased over the years along with increased urbanization and environmental pollutants thought to be some of the leading causes of the disease. Understanding the pathophysiology of AR is crucial in the development of novel therapies to treat this incurable disease that often comorbids with other airway diseases. Hence in this mini review, we summarize the well-established yet vital aspects of AR. These include the epidemiology, clinical and laboratory diagnostic criteria, AR in pediatrics, pathophysiology of AR, Th2 responses in the disease, as well as pharmacological and immunomodulating therapies for AR patients.